2019
DOI: 10.3847/1538-4357/ab0a71
|View full text |Cite
|
Sign up to set email alerts
|

Chandra-HETGS Characterization of an Outflowing Wind in the Accreting Millisecond Pulsar IGR J17591–2342

Abstract: IGR J17591−2342 is an accreting millisecond X-ray pulsar discovered in 2018 August in scans of the Galactic bulge and center by the INTEGRAL X-ray and gamma-ray observatory. It exhibited an unusual outburst profile with multiple peaks in the X-ray, as observed by several X-ray satellites over three months. Here we present observations of this source performed in the X-ray/gamma-ray and near infrared domains, and focus on a simultaneous observation performed with the Chandra-High Energy Transmission Gratings Sp… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
27
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(34 citation statements)
references
References 45 publications
6
27
1
Order By: Relevance
“…Winds with similar properties (velocities, ionisation parameters) have been discovered in other neutron star binary systems such as GX 13+1 (Ueda et al 2004), IGR J17480-2446 (Miller et al 2011) and IGR J17591-2342 (Nowak et al 2019). The difference between these three and Her X-1 is that the column density observed in Her X-1 is significantly lower during most observations and thus the absorption strength is correspondingly lower.…”
Section: Obs Idsupporting
confidence: 57%
“…Winds with similar properties (velocities, ionisation parameters) have been discovered in other neutron star binary systems such as GX 13+1 (Ueda et al 2004), IGR J17480-2446 (Miller et al 2011) and IGR J17591-2342 (Nowak et al 2019). The difference between these three and Her X-1 is that the column density observed in Her X-1 is significantly lower during most observations and thus the absorption strength is correspondingly lower.…”
Section: Obs Idsupporting
confidence: 57%
“…In addition, a broad iron line produced by the reflection of the X-ray photons onto the inner regions of the accretion disk surrounding the compact object was sometimes also observed (Papitto et al, 2009;Cackett et al, 2009;Sanna et al, 2017bSanna et al, , 2018cDi Salvo et al, 2019). In at least one case, high spectral resolution observations carried out with the gratings on-board Chandra were able also to detect outflows from the outer regions of the accretion disk (Nowak et al, 2019), and to provide hints of an expanding hot corona with high outflow velocities also in the case of IGR J00291+0034 (Paizis et al, 2005).…”
Section: The Hard X-ray Spectra Of Amspsmentioning
confidence: 98%
“…As such, the initial radio observations of Russell et al (2018a) were performed close in time, but weeks after the first bright peak of the outburst (Figure 1), and did not sample the later X-ray bright peaks that were observed (Sanchez-Fernandez et al 2018;Kuiper et al 2018;Ray et al 2018). Nowak et al (2019) presented high-resolution spectroscopy using the Chandra X-ray Observatory, performed during the start of the second peak of the outburst (see red dotted vertical line in Figure 1) and demonstrated evidence for an outflowing wind in IGR J17591−2342. The AMXP SAX J1808.4−3658 also showed evidence for a wind (Pinto et al 2014).…”
Section: Igr J17591−2342mentioning
confidence: 99%
“…Such a scenario could also be a potential explanation for the large variability of the radio emission of IGR J17591−2342, which appears to be the brightest during the first three radio epochs. Nowak et al (2019) found winds using a Chandra observation that was performed 2 days before the third and brightest ATCA observation. This remains a tentative possibility, since only one high-spectral resolution observation was performed during the 2018 outburst of IGR J17591−2342; thus, the direct influence of Xray winds on radio brightness could not be further explored.…”
Section: Radio-x-ray Relationmentioning
confidence: 99%